Communal Reading in the Time of Jesus : a Window into Early Christian Reading Practices - Wright, Brian J. (Project Muse, 2018)
Much of the contemporary discussion of the Jesus tradition has focused on aspects of oral performance, storytelling, and social memory, on the premise that the practice of communal reading of written texts was a phenomenon documented no earlier than the second century CE. Brian J. Wright overturns that premise by examining evidence that demonstrates communal reading events in the first century. Wright disproves the simplistic notion that only a small segment of society in certain urban areas could have been involved in such communal reading events during the first century; rather, communal reading permeated a complex, multifaceted cultural field in which early Christians, Philo, and many others participated. His study thus pushes the academic conversation back by at least a century and raises important new questions regarding the formation of the Jesus tradition, the contours of book culture in early Christianity, and factors shaping the transmission of the text of the New Testament. These fresh insights have the potential to inform historical reconstructions of the nature of the earliest churches as well as the story of canon formation and textual transmission.